Piercing the darkness - Peretti, Frank E. (Tyndale House Publishers, 2002)
It all begins in Bacon's Corner, a tiny farming community far from the interstate ... An attempted murder, a case of mistaken - or covered up? - identity, and a ruthless lawsuit against a struggling school. Sally Beth Roe, a young loner, finds herself caught in the middle of these bizarre events, fleeing for her life while trying to recall her dark past. Heart- stopping action, a penetrating glimpse into our times, and a vivid portrayal of the power of redemption.